Teaching and learning enhancement based on Telegram social media tool / Mohammad Nizam Ibrahim ... [et al.] - Ibrahim, Mohammad Nizam; Norsaal, Emilia; Abdullah, Mohd Hanapiah; Che Soh, Zainal Hisham (Universiti Teknologi MARA, Perlis, 2016)
This study investigates a perception of students on the implementation of a Telegram application as an enhancement tool for teaching and learning. The population of this study is 66 students who are studying a Bachelor of Electrical and Electronic Engineering programme at Universiti Teknologi MARA (Pulau Pinang). The study has been conducting on Mac – September 2015 academic semester. The students have been using the Telegram tool in their teaching and learning process during the academic semester. Next, an online survey consisting of a number of agreement-level questions and open-ended questions are developed in google form. At the end of the semester, the form has been distributed to students via a link created in Telegram discussion groups to collect students’ valuable feedback. The student feedbacks have been analyzed to obtain the results of their perception on the Telegram application as an enhancement tool for teaching and learning process. The results show that Telegram application support teaching and learning enhancement by providing a quick way and easy platform for sharing information.